Improving Maritime Students’ English Grammar Through Quizizz Gamification App: A Bloom’s Taxonomy-Based Approach at AMI AIPI Makassar - Rafiq, Muhamad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study explores the impact of integrating the Quizizz gamification platform with Bloom’s Taxonomy to improve the English grammar of third-semester maritime cadets at AMI AIPI Makassar. Employing a quasi-experimental mixed-method design, the research involved 43 students, divided into an experimental group (Nautika, n = 22) and a control group (Teknika, n = 21). Over six instructional sessions, the experimental group engaged with grammar activities designed according to Bloom’s cognitive levels using the Quizizz application, while the control group received conventional instruction. The results demonstrated a statistically significant enhancement in the grammar proficiency of the experimental group, which achieved a mean post-test score of 82.5 (SD = 5.8), notably higher than the control group’s 70.2 (SD = 5.5). Statistical analyses using paired and independent t-tests confirmed this difference as highly significant (p < 0.001). Furthermore, student feedback collected through perception questionnaires indicated strong engagement and positive attitudes toward the gamified approach, especially appreciating features such as leaderboards and real-time feedback. These findings highlight the pedagogical potential of integrating gamification with a structured cognitive framework such as Bloom's Taxonomy to enhance linguistic competence and student motivation in the context of English.